2021
DOI: 10.1007/s40279-021-01573-z
|View full text |Cite|
|
Sign up to set email alerts
|

Training During the COVID-19 Lockdown: Knowledge, Beliefs, and Practices of 12,526 Athletes from 142 Countries and Six Continents

Abstract: Objective Our objective was to explore the training-related knowledge, beliefs, and practices of athletes and the influence of lockdowns in response to the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods Athletes (n = 12,526, comprising 13% world class, 21% international, 36% national, 24% state, and 6% recreational) completed an online survey that was available from 17 May to 5 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
157
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(170 citation statements)
references
References 43 publications
(53 reference statements)
10
157
0
3
Order By: Relevance
“…The current data revealed that 16% of the increase in perceived stress during lockdown was associated with sport classification ( Table 2 ). These findings may also be related to reduced training motivation during lockdown [ 3 , 4 , 22 ]. Decreased training motivation may impair an individual’s ability to perform the training exercises appropriately and reduce the choice of exercises/activities [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current data revealed that 16% of the increase in perceived stress during lockdown was associated with sport classification ( Table 2 ). These findings may also be related to reduced training motivation during lockdown [ 3 , 4 , 22 ]. Decreased training motivation may impair an individual’s ability to perform the training exercises appropriately and reduce the choice of exercises/activities [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has affected the ability of many athletes to travel, train and compete. There is emerging evidence concerning the detrimental physical and mental effects of the pandemic [ 1 , 2 ], including on athletic populations [ 3 , 4 ]. The detrimental effects of lockdowns appear to vary among individuals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endurance athletes are known for performing high training volumes throughout the year to maintain cardiovascular fitness and to attain peak performance for the competition period [ 1 , 2 , 3 ]. The COVID-19 pandemic has been reported to impact the athletes’ training, competition, and recovery routines [ 4 , 5 , 6 , 7 , 8 , 9 ]. Washif et al [ 4 ] analyzed the training habits of 12,526 athletes of various performance levels (i.e., recreational to professional) from 142 countries and six continents during the COVID-19 confinement.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has been reported to impact the athletes’ training, competition, and recovery routines [ 4 , 5 , 6 , 7 , 8 , 9 ]. Washif et al [ 4 ] analyzed the training habits of 12,526 athletes of various performance levels (i.e., recreational to professional) from 142 countries and six continents during the COVID-19 confinement. Despite reductions in training session frequency, most athletes focused on maintenance of general endurance and strength rather than exploiting sports-specific training [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%